Local Community Based Tourism Village Development Strategy in Buluh Awar Tourism Village Deli Serdang District - Pardede, Tarida; Sebastiana, Sumihar; Zaitun (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Buluh Awar Tourist Village is one of the tourist villages that were established by Bupati Deli Serdang on SK Bupati in 2022 and 2023 managed to obtain the nomination of the 300 Great Anugerah Village Tourism of Indonesia after attending the contest of Adwi 2023. The village of Buluh Awar is known for its cultural tourism and is the zero entry point of Christianity into the Karo land. The village is located in the Sibolangit district of Deli Serdang. The purpose of writing this thesis is to describe the tourist destination components that exist in Buluh Awar Village, to identify the level of irritation of the local community to the development of tourism in the Buluh Tourism Village, then identify local community participation in tourism development in the village of Buluh aware as well as to design a strategy of development of the village tourism based on the local community in the tourism village. To meet these objectives qualitative and quantitative descriptive analysis using Buhalis's theory, 2000 on the component of Tourist Destinations, Doxey Irridex's theory (1975) on the level of public irritation to the development of tourism, then Tosun's theory (1999) related to the rate of participation of tourists. Based on the results of the analysis, found the tourist destination component in Buluh Awar Tourist Village that most requires attention is the component amenity and ancillary service, and the level of irritation of the community after being analyzed is in the position of Euforia, whereas for the rate of participation of its community is passive participation. Related recommendations for the involvement of local communities can be more active by forming tourism communities such as Pokdarwis as a container for communities to accommodate ideas or ideas related to tourism development and engage communities actively in tourism activities under strategy 1). Identify Local Champion. 2). Make a memorandum of understanding about the distribution of roles and functions of stakeholders. 3). Strengthening the capacity of the community. 4). Institutional strengthening. 5). Real action that can be implemented in the Tourist Village Buluh Awar. Keywords: strategy, development, Tourism Village, local community, community participation.